Hepatitis B Virus X Protein Upregulates SREBP2 to Modulate Autophagy in Hepatocellular Carcinoma - Qiuyan Lin; Yongxu Lin; Yongzhu Huang; Mingrong Wang; Xiaoxia Xie; Weiqi Cai; Qilan Guo; Pingying Jiang; Yuanlin Qi; Dan Li (Cancer Medicine)
ABSTRACT Background The interaction between Hepatitis B virus X protein (HBx) and sterol regulatory element binding protein 2 (SREBP2) in modulating autophagy to influence inflammation and tumorigenesis is not fully understood. This research seeks to clarify the regulatory role of HBx in hepatocyte autophagy through SREBP2. Methods The study employed TCGA and GEO databases to investigate the expression of SREBF2 and autophagy‐related proteins in liver cancer. Various experimental techniques, including dual‐luciferase reporter assays, immunohistochemistry, Western blotting, immunofluorescence, GFP‐mRFP‐LC3 puncta analysis, transmission electron microscopy, and Fillipin III staining, were conducted on HBV‐associated liver cancer tissues, HBV transgenic mice, and several liver cancer cell lines to assess the levels of HBx, SREBP2, autophagy, and cholesterol, respectively, as well as to explore potential associations between these factors. Results Bioinformatics analysis suggested up‐regulation of SREBP2 and autophagy‐associated genes in HBV‐associated liver cancer. Elevated levels of cholesterol, SREBP2, and autophagy flux were detected in HBV‐associated liver cancer tissues as compared to adjacent tissues. HBV transgenic mice had higher cholesterol, SREBP2, and autophagy levels than wild‐type mice. HBx activated the SREBP2 promoter to enhance its transcription and nuclear translocation. HBx knockdown down‐regulated SREBP2 expression and nuclear translocation levels in HepG2.2.15‐siHBx cells. HepG2.2.15 and HepG2‐HBx showed more autolysosomes than HepG2 cells; furthermore, HepG2.2.15‐siHBx cells had fewer autolysosomes than HepG2.2.15 cells. Conclusions This research highlights that HBx upregulates SREBP2 and increases autophagic flux, accompanied by changes in cholesterol metabolism, which offers an additional theoretical foundation to elucidate that chronic HBV infection causes abnormal lipid metabolism and induces tumorigenesis.